2015
DOI: 10.1098/rsif.2014.1055
|View full text |Cite
|
Sign up to set email alerts
|

Lateral assembly of N-cadherin drives tissue integrity by stabilizing adherens junctions

Abstract: Cadherin interactions ensure the correct registry and anchorage of cells during tissue formation. Along the plasma membrane, cadherins form inter-junctional lattices via cis-and trans-dimerization. While structural studies have provided models for cadherin interactions, the molecular nature of cadherin binding in vivo remains unexplored. We undertook a multi-disciplinary approach combining live cell imaging of three-dimensional cell assemblies (spheroids) with a computational model to study the dynamics of N-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Unlike genetic or pharmacological perturbations that may have offtarget or deleterious effects (e.g., on protein stability), these nanopatterned substrates allow receptor clustering to be perturbed in a purely physical way, thereby avoiding such effects. More importantly, although mutation of the cis-interaction interface in E-cadherin results in a change in the dynamics of E-cadherin clusters, cells nevertheless form E-cadherin clusters (22,52,(67)(68)(69), and thus the cismutant E-cadherin may not be useful for investigating the role of E-cadherin clustering. Therefore, the use of nanopatterned substrates, as described here, appears to be the only way to definitively manipulate micron-scale E-cadherin assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike genetic or pharmacological perturbations that may have offtarget or deleterious effects (e.g., on protein stability), these nanopatterned substrates allow receptor clustering to be perturbed in a purely physical way, thereby avoiding such effects. More importantly, although mutation of the cis-interaction interface in E-cadherin results in a change in the dynamics of E-cadherin clusters, cells nevertheless form E-cadherin clusters (22,52,(67)(68)(69), and thus the cismutant E-cadherin may not be useful for investigating the role of E-cadherin clustering. Therefore, the use of nanopatterned substrates, as described here, appears to be the only way to definitively manipulate micron-scale E-cadherin assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…These estimates provide a simple metric to classify and categorize tumour spheroids, which has potential application to high-throughput comparative assays [8][9][10]. For example, the PCF method could be used to investigate population-level variability in the size of the necrotic zone by using a larger sample of mature tumour spheroids from the same cell line, grown from the same number of seeded cells.…”
Section: Discussionmentioning
confidence: 99%
“…The schematic diagram of figure 1 illustrates the necrotic, quiescent and proliferative zones within a tumour spheroid. Identifying and quantifying these three regions is important in the analysis of comparative assays on tumour spheroids [8][9][10] and mathematical models of the tumour growth process [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For the experiments, spheroid formation of different cell types (21,22) or the same cell type under different conditions is monitored. Potential variations for the same cell type are the expression of different binding proteins (23,24) or the application of adhesion molecule functional blocking antibodies (21). Studying spheroid formation of cells transfected with wild type or mutant forms of N-cadherin revealed that different cadherin binding sites are responsible for different cell adhesion mechanisms such as the initial binding and the stabilization of an adherence junction.…”
Section: First Workflow: Cell Biologymentioning
confidence: 99%